EXPERIMENTAL AND CLINICAL PHARMACOLOGY OF RIFAXIMIN SELECTIVE ENTERIC ANTIBIOTIC - article editorial (Union of pediatricians of Russia, 2008)
Solvay pharma expands its product portfolio, by launching alfa normix (rifaximin) for the treatment of the gastroenteric infections. Alfa normix is a non-systemic broad-spectrum antibiotic to treat acute gastroenteric infections and is prescribed for the travelers suffering from diarrhea, the overgrowth of microorganisms in the intestinal tract, hepatic encephalopathy, symptomatic uncomplicated diverticular disease of the segmented intestine, and chronic inflammation of the intestinal tract, as well as to prevent the infectious complications in the event of the colorectal surgeries. The first medication deliveries to Russia are scheduled for march 2008.Key words: rifaximin, infectious diarrhea, enteric infections.